2016
DOI: 10.1103/physreve.93.013116
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical properties of turbulent premixed flames and other corrugated interfaces

Abstract: This study focuses on the geometrical properties of turbulent flame fronts and other interfaces. Toward that end, we use an original tool based on proper orthogonal decomposition (POD), which is applied to the interface spatial coordinates. The focus is mainly on the degree of roughness of the flame front, which is quantified through the scale dependence of its coverage arclength. POD is first validated by comparing with the caliper technique. Fractal characteristics are extracted in an unambiguous fashion usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 97 publications
(204 reference statements)
1
22
0
Order By: Relevance
“…have also shown that the flame speed/flame stretch correlation is strongly affected by the flow forcing frequency and can even vanish at high forcing frequencies in agreement with the theoretical predictions of Joulin (1994), Clavin & Joulin (1997). Transient effects are also important for characterizing the flame geometrical properties, for instance flame stretch (Thiesset et al 2017). (iv) These effects might be smoothed when applying surface averaging.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…have also shown that the flame speed/flame stretch correlation is strongly affected by the flow forcing frequency and can even vanish at high forcing frequencies in agreement with the theoretical predictions of Joulin (1994), Clavin & Joulin (1997). Transient effects are also important for characterizing the flame geometrical properties, for instance flame stretch (Thiesset et al 2017). (iv) These effects might be smoothed when applying surface averaging.…”
Section: Introductionsupporting
confidence: 74%
“…2.1. The flame-vortex interaction burner (FVIB) Experiments are carried out at ICARE, Orléans, in the burner used by Thiesset et al (2017) and presented in figure 1. Fuel and oxidizer are mixed before being fed through the side of the burner.…”
Section: Tools Of Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…developed and tested by Thiesset et al (2016) for exactly this purpose. The function smoothly connects the asymptotes L = const.…”
Section: Resultsmentioning
confidence: 99%